Using subjective and objective measures to predict level of reading fluency at the end of first grade. Issue 3 (3rd April 2018) - Morris, Darrell; Pennell, Ashley M.; Perney, Jan; Trathen, Woodrow
Abstract : This study compared reading rate to reading fluency (as measured by a rating scale). After listening to first graders read short passages, we assigned an overall fluency rating (low, average, or high) to each reading. We then used predictive discriminant analyses to determine which of five measures—accuracy, rate (objective); accuracy, phrasing, pace (subjective)—would best predict our fluency ratings. The objective measure of rate and the subjective measure of phrasing were clearly the best predictors, classifying approximately 90% of the cases correctly. The results support the use of reading rate as a proxy for reading fluency in first grade.